Psychometric properties of a German version of the Young Diagnostic Questionnaire (YDQ) in two independent samples of adolescents - Wartberg, Lutz; Parzer, Peter; Fischer-Waldschmidt, Gloria; Brunner, Romuald; Kaess, Michael (International journal of mental health and addiction, 2017)
The Young Diagnostic Questionnaire (YDQ) is the most frequently used unidimensional measure to assess pathological Internet use. To date, investigations on the factorial validity of the YDQ using confirmatory factor analysis (CFA) are not available in the scientific literature. Empirical findings on the psychometric properties of the German translation of the YDQ are also lacking. Data were collected on two German samples of 1444 and 2713 adolescents. A confirmatory factor analysis (CFA) was conducted. We also calculated reliability coefficients and correlations between the YDQ and external criteria of Internet use. The models showed excellent global goodness-of-fit and satisfying local parameters. A unidimensional model seems to fit the data very well. We observed rather low reliability coefficients. The results indicate an acceptable construct validity of the German YDQ. The German version of the YDQ is a suitable instrument for measuring pathological Internet use in adolescent populations.